2017
DOI: 10.1377/hlthaff.2016.0840
|View full text |Cite
|
Sign up to set email alerts
|

Little Evidence Exists To Support The Expectation That Providers Would Consolidate To Enter New Payment Models

Abstract: Provider consolidation has been associated with higher health care prices and spending. Prevailing wisdom assumes that payment reform will accelerate consolidation, especially between physicians and hospitals and among physician groups, as providers position themselves to bear financial risk for the full continuum of patient care. Drawing from a number of data sources from 2008 onward, we examined the relationship between Medicare’s Accountable Care Organization (ACO) programs and provider consolidation. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…4,5 However, a recent study found no association between local market ACO penetration and increased vertical integration. 6 Vertical integration could instead result from a desire by hospitals and physicians to earn higher revenues. If a hospital controls a large share of physicians in a region, the hospital may be able to negotiate higher prices for its services from insurers, due to the facility's stronger bargaining power.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, a recent study found no association between local market ACO penetration and increased vertical integration. 6 Vertical integration could instead result from a desire by hospitals and physicians to earn higher revenues. If a hospital controls a large share of physicians in a region, the hospital may be able to negotiate higher prices for its services from insurers, due to the facility's stronger bargaining power.…”
Section: Introductionmentioning
confidence: 99%
“…That said, we do not find any evidence of a decrease in severe maternal morbidity with Catholic ownership that would support an overall conclusion of improved quality. Current literature suggests that this growth in mergers and affiliation changes are part of a broader trend in hospital consolidation likely driven by multiple factors such as economies of scale, financial distress, desires to expand market power, and risk management strategies in response to health care reform (Dafny 2014, Uttley and Khaikin 2016, Neprash et al 2017. We test our identifying assumption by estimating how changes in ownership affect the composition of reproductive patients, hospital characteristics, and controlling for changes in unemployment in the county where the hospital is located.…”
mentioning
confidence: 99%
“…3,6,27 Other research, however, has demonstrated that vertical integration preceded initiation of alternative payment models. 28 The increased likelihood of physician practices to accept Medicaid after vertical integration has been previously demonstrated. 8,11,12 Hospitals that consolidate are more likely to be large or major teaching hospitals and less likely to be for-profit institutions, 29 and large hospital systems are required to treat all acute patients due to regulations such as the Emergency Medical Treatment and Labor Act of 1986.…”
Section: Discussionmentioning
confidence: 94%